(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
The article examines the purposeful use of means of development of coordination abilities of 8-10-year-old karateka at the stage of initial training, the manifestation of which is a guarantee of success at the next stages of multi-year training. The purpose of the study is to determine the influence of the proposed method of development of coordination abilities of young karate players 8-10 years old, at the stage of initial training, on the level of preparedness of athletes. The analysis of the obtained results shows that under the influence of the proposed method of development of coordination abilities at the stage of initial training, indicators of physical development are better in the experimental group than in the control group. Statistically significant differences between the control and experimental groups were established according to the Student’s test at p<0.05 in the tests: jumps on the coordination shot 5 m facing forward t=4.49; jumping on the coordination shot 5 m with the back forward t=2.99; jumping on a rope (rotate arms forward) in 30 s t=4.23; sprint with a sharp change in the direction of movement t= 2.44; performance of 12 punches and kicks at different levels and in different directions t=2.29; sprint with a sharp change in the direction of movement and hitting targets t=2.96; 15 blows of ushiro-ura-mawasha t=2.05. The results of arithmetic mean indicators when performing tests in the experimental group are better than in the control group. In the shuttle run test 4×9 m by 7.9 %; jumping on the coordination shot 5 m facing forward – 15.13 %; jumping on the coordination shot 5 m with the back forward – 18.5 %; jumping on a rope (turning hands forward) in 30 seconds – 23.6 %; jumping on a rope (turning the hands backwards) in 30 seconds – 12.5%; sprint with a sharp change in the direction of movement – 18.95%; motor reaction speed – 14.5 %; 15 wide-hurrah-mawasha shots for 16.18%; execution of mawasha blows in 20s after spinning around oneself for 20 s – 14.39%; performance of 12 punches and kicks at different levels and in different directions – 17.83 %; sprint with a sharp change in the direction of movement and execution of blows on targets – 18.22 %; tossing a tennis ball and performing a kizami-gyaku kick in 30 s – 19.52 %. Conclusions. For novice karatekas, the development of coordination skills is of great importance. The implementation of any technical technique is built on the basis of old coordination ties. The greater the reserve of various movement skills and skills an athlete has at the initial stage, the more successful will be the mastering of the technique and its use in changing situations in further sports activities. to be used by specialists in the field of physical culture and sports and allow choosing optimal training loads that will contribute to the effectiveness of training process management and thus increase sportsmanship of athletes.